POSSIBILITIES OF ENHANCED EXTERNAL COUNTERPULSATION USING IN CLINICAL PRACTICE - Z. A. Mamieva; A. S. Lishuta; Yu. N. Belenkov; E. V. Privalova; A. O. Yusupova; S. M. Rykova (Столичная издательская компания, 2017)
Possibilities and prospects for the clinical use of enhanced external counterpulsation (EECP), which has long established itself throughout the world, are discussed in the article. Historical background, as well as the development stages of EECP for the treatment of patients with coronary heart disease (CHD) and chronic heart failure (CHF) are considered. The mechanism of action of the EECP and the main hemodynamic, neurohumoral and tissue effects that justify its use are presented. The effect of EECP on endothelial function and coronary reserve, disorders of which occurs in the majority of cardiovascular diseases, is considered separately. Treatment of patients with CHD, including complicated by CHF, are the most studied indications for EECP using in medical practice. The evidence base for treatment of patients with these disorders by EECP is presented in the article. Prospects for the EECP application in other areas of medicine are also presented.